1999
DOI: 10.1007/s001270050156
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing mental disorders in primary care: the General Health Questionnaire (GHQ) and the Symptom Check List (SCL-90-R) as screening instruments

Abstract: GHQ-12 and SCL-90-R appeared to be useful tools for identifying mental disorders in primary care practice and research. The use of GHQ-12 or SCL-90-R, employed as a first step, supplemented by a second-stage interview, may enhance the detection rate of mental disorder in primary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
9

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(146 citation statements)
references
References 10 publications
3
134
0
9
Order By: Relevance
“…The Chinese version of symptom checklist-90 (SCL-90) (Wang, 1984), a 90-item multidimensional self-report inventory aiming to evaluate a broad range of psychological problems and symptoms of psychopathology, was adopted as the major measurement for psychological status. The reliability, validity and utility of SCL-90 have been proved not only by psychiatric and psychological studies (Peveler et al, 1990;Schimitz et al, 1999;Prins et al, 2001), but also been demonstrated by studies in cancer patients (Derogatis et al, 1983;Tross et al, 1996;Lerman et al, 2011). The data from SCL-90 were calculated and compared with the normal range in Chinese reported by Jin et al (1986.…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese version of symptom checklist-90 (SCL-90) (Wang, 1984), a 90-item multidimensional self-report inventory aiming to evaluate a broad range of psychological problems and symptoms of psychopathology, was adopted as the major measurement for psychological status. The reliability, validity and utility of SCL-90 have been proved not only by psychiatric and psychological studies (Peveler et al, 1990;Schimitz et al, 1999;Prins et al, 2001), but also been demonstrated by studies in cancer patients (Derogatis et al, 1983;Tross et al, 1996;Lerman et al, 2011). The data from SCL-90 were calculated and compared with the normal range in Chinese reported by Jin et al (1986.…”
Section: Methodsmentioning
confidence: 99%
“…Cut-off score is the value at which a psychological disorder is indicated on the given measure. These values were obtained from Goldberg (1978) and Schmitz, Kruse, Heckrath, Alberti and Tress (1999) for the GHQ-12; Beck, Steer and Brown (1996) for the BDI-II; and, Schmitz et al (1999) for the GSI.…”
Section: Aaq-ii Scores From Values (Or Cut-off Scores) That Indicate mentioning
confidence: 99%
“…25,40 GHQ-12 has been shown to be a valid screening tool for anxiety and depression diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, third edition (revised). 41 A further limitation is that GHQ-12 score was only recorded at baseline and there was no reassessment of psychological distress via questionnaire.…”
Section: Strengths and Limitationsmentioning
confidence: 99%